(2x+1)3=9X81
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{10^9\cdot81^{10}}{8^4\cdot25^3\cdot9^{10}}=\dfrac{2^9\cdot5^9\cdot3^{40}}{2^{12}\cdot5^6\cdot3^{20}}=\dfrac{5^3\cdot3^{20}}{2^3}\)
81 x 152 + 100 x 19 + 9 x 81 - 8 x 61 = 12312 + 1900 + 729 - 488
= 14453
Nhớ click cho mik nha !!!!!!!!!!!!!!!!!!!!!!
1: \(=6x^2+2x-15x-5-x^2+6x-9+4x^2+20x+25-27x^3-27x^2-9x-1\)
=-27x^3-18x^2+4x+10
2: =4x^2-1-6x^2-9x+4x+6-x^3+3x^2-3x+1+8x^3+36x^2+54x+27
=7x^3+37x^2+46x+33
5:
\(=25x^2-1-x^3-27-4x^2-16x-16-9x^2+24x-16+\left(2x-5\right)^3\)
\(=8x^3-60x^2+150-125+12x^2-x^3+8x-60\)
=7x^3-48x^2+8x-35
1) `2x(3x-1)-(2x+1)(x-3)`
`=6x^2-2x-2x^2+6x-x+3`
`=4x^2+3x+3`
2) `3(x^2-3x)-(4x+2)(x-1)`
`=3x^2-9x-4x^2+4x-2x+2`
`=-x^2-7x+2`
3) `3x(x-5)-(x-2)^2-(2x+3)(2x-3)`
`=3x^2-15x-(x^2-4x+4)-(4x^2-9)`
`=3x^2-15x-x^2+4x-4-4x^2+9`
`=-2x^2-11x+5`
4) `(2x-3)^2+(2x-1)(x+4)`
`=4x^2-12x+9+2x^2+8x-x-4`
`=6x^2-5x+5`
g: Ta có: \(3\left(2x-1\right)\left(3x-1\right)-\left(2x-3\right)\left(9x-1\right)=0\)
\(\Leftrightarrow3\left(6x^2-5x+1\right)-\left(18x^2-29x+3\right)=0\)
\(\Leftrightarrow18x^2-15x+3-18x^2+29x-3=0\)
\(\Leftrightarrow14x=0\)
hay x=0
c: \(\left(2x+3\right)^2+\left(2x-3\right)^2-\left(2x+3\right)\left(2x-3\right)\)
\(=4x^2+12x+9+4x^2-12x+9-\left(4x^2-9\right)\)
\(=8x^2+18-4x^2+9=4x^2+27\)
d: \(\left(x-1\right)\cdot\left(x^2+x+1\right)-\left(2x+3\right)\left(4x^2-6x+9\right)\)
\(=\left(x-1\right)\left(x^2+x\cdot1+1^2\right)-\left(2x+3\right)\left[\left(2x\right)^2-2x\cdot3+3^2\right]\)
\(=x^3-1-8x^3-27=-7x^3-28\)
e: \(\left(x+1\right)^3-\left(x-1\right)^3-6x^2\)
\(=x^3+3x^2+3x+1-6x^2-\left(x^3-3x^2+3x-1\right)\)
\(=x^3-3x^2+3x+1-x^3+3x^2-3x+1\)
=2
a: Ta có: \(3x\left(2x+1\right)+\left(2x-3\right)\left(x+1\right)\)
\(=6x^2+3x+2x^2+2x-3x-3\)
\(=8x^2+2x-3\)
\(\Leftrightarrow2x+1=9\)
hay x=4
x=4